DIPLOMASI FEMINA GROUP MEMPROMOSIKAN BATIK TENUN DI PASAR INTERNASIONL - Sihombing, Samuel; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research aims to find out about Indonesian diplomacy from the implementation of the Jakarta Fashion Week event to promote woven batik. This research was written using the group level of analysis, cultural concepts, diplomacy theory by Nicholas J. Cull which states that diplomacy can be done in various ways. Diplomacy itself is an art in leading and providing policies towards one's country. The data collection technique in this research uses a literature review which takes references from various existing sources. Apart from that, we also adopt from literature in the library that is directly seen and read. This research was also compiled from various sources, such as journal articles, and others, making this research one in writing. From the results of this research, it can be concluded that Indonesia's diplomacy through the Jakarta Fashion Week event in promoting woven batik can be said to be successful. Because if you look at the data, batik sales in Indonesia and the international market have reached their target. However, special attention needs to be paid so that the development and sales of woven batik in Indonesia continue to increase. Keywords: Diplomacy, Jakarta Fashion Week, International Market Woven Batik